Recycling method of waste polyester alcoholysis by-products

By using porous boron nitride@crown ether hybrid material to efficiently adsorb and chelate potassium ions during the alcoholylation of waste polyester, the regeneration and utilization problems caused by potassium ion residue are solved, and efficient potassium ion removal and quality improvement of regenerated resins are achieved.

CN119798778AActive Publication Date: 2025-04-11ZHEJIANG SCI-TECH UNIV

Patent Information

Application Number
CN202510304340.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-11
Estimated Expiration
2045-03-14

AI Technical Summary

Technical Problem

During the glycol glycol of waste polyester, potassium ion residues make it difficult to recycle and utilize the alcoholylation by-products, and the existing methods are not effective.

Method used

Porous boron nitride @ crown ether hybrid material is prepared by hydrothermal deposition and ball milling treatment. Its unique powder-like porous structure is used to efficiently adsorb and chelate potassium ions to achieve efficient removal of potassium ions.

Benefits of technology

It realizes efficient removal of potassium ions in the alcoholylation by-product of waste polyester, improves the polymerization stability and product quality of the regenerated resin, and promotes the recycling and utilization of waste polyester.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a recycling method of waste polyester alcoholysis byproducts, which comprises the following steps: S1) mixing porous boron nitride micro powder, crown ether and water, carrying out hydrothermal deposition treatment, and freeze-drying to obtain a solid powdery material; carrying out ball milling on the solid powdery material to obtain a porous boron nitride and crown ether hybrid material; and S2) carrying out alcoholysis reaction on waste polyester, ethylene glycol and a catalyst potassium carbonate, and adding the hybrid material into the obtained reaction liquid. The invention also provides a preparation method of the porous boron nitride and crown ether hybrid material. In the recycling method of the waste polyester alcoholysis by-product, the introduction of the porous boron nitride and crown ether hybrid material combines the strong adsorbability of metal ions of porous BN and the selective metal complexation of crown ether, so that the removal rate of potassium ions in the alcoholysis reaction liquid is increased; the molecular chain end-capping effect caused by potassium ions in the subsequent polymerization process of a depolymerization product is overcome, and the method has important industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste polyester recovery, in particular to a method for recycling waste polyester alcoholysis byproducts. Background Art

[0002] Polyethylene terephthalate (PET), as a thermoplastic polyester material, has been widely used in many fields such as fibers, plastics, and films due to its excellent heat resistance, mechanical properties, chemical stability, electrical insulation, and wear resistance. However, with the continuous expansion of the application scope of PET products and the continuous growth of production capacity, the accumulation of waste PET is also gradually increasing, which not only leads to serious waste of resources, but also causes significant pollution to the environment. The use of chemical recycling technology to depolymerize waste PET into small molecular monomers and prepare high-performance recycled products through subsequent polymerization processes has important economic and practical significance for the recycling of waste PET. Among many chemical recycling methods, ethylene glycol alcoholysis can effectively depolymerize waste PET into dihydroxyethyl terephthalate (BHET). The reaction conditions are mild, the safety is good, and the product yield is high, making it one of the key technologies for recycling waste PET.

[0003] However, in the glycol hydrolysis process of waste polyester, the PET molecular chain break position is random and the depolymerization reaction is often incomplete. In addition, the product BHET is prone to etherification reaction at high temperature, resulting in the production of a series of low-polymerization byproducts in addition to BHET. In addition, potassium carbonate, as an economical, environmentally friendly, low-toxic and efficient catalyst, has been widely used in depolymerization reactions, but due to its easy solubility in alcohol depolymerization liquids, it will remain in the depolymerization byproducts in small amounts. When these depolymerization byproducts are used as raw materials to prepare regenerated resins, the potassium ions released by the residual potassium carbonate as Lewis acid will seriously inhibit the molecular chain viscosity increase reaction. At the same time, potassium ions will also react with the ester groups on the resin molecular chain to induce molecular chain degradation, seriously affecting the stability of the polymerization reaction and the increase in polymer viscosity, making it difficult for a large number of depolymerization byproducts to be recycled. Although attempts have been made to shield potassium ions by adding metal chelators such as crown ethers online, the effect is not ideal, and such metal chelators will block the active centers of the polymerization catalyst during the reaction, further reducing the polymerization efficiency.

[0004] Therefore, it is urgent to invent a new material and method to achieve efficient and selective removal of potassium ions in the process of chemical recovery of waste polyester. Summary of the invention

[0005] The technical problem solved by the present invention is to provide a method for recycling waste polyester alcoholysis by-products. The method provided by the present application can efficiently absorb and shield potassium ions and has a high potassium ion removal rate.

[0006] In view of this, the present application provides a method for recycling waste polyester alcoholysis byproducts, comprising the following steps:

[0007] S1) mixing porous boron nitride micropowder, crown ether and water, performing hydrothermal deposition treatment and freeze drying to obtain a solid powder material;

[0008] Ball milling the solid powder material to obtain a porous boron nitride@crown ether hybrid material;

[0009] S2) performing alcoholysis reaction on waste polyester, ethylene glycol and catalyst potassium carbonate, and adding the hybrid material to the obtained reaction solution to remove potassium ions in the reaction solution.

[0010] Preferably, the preparation method of the porous boron nitride powder is specifically as follows:

[0011] The boron source, the nitrogen source, the pore-forming agent and water are mixed, and then heated and dried to obtain a boron nitride precursor;

[0012] The boron nitride precursor is ground and then calcined to obtain porous boron nitride powder.

[0013] Preferably, the boron source includes one or more of boric acid, ammonia borane, metaboric acid, boron chloride, boron oxide, boron sulfide and sodium borohydride; the nitrogen source includes one or more of urea, melamine, sodium azide, dicyandiamide and sodium amide; the pore-forming agent includes one or more of zinc acetate, nickel sulfate, cobalt sulfate, iron sulfate, copper sulfate and zinc sulfate; the mass ratio of the boron source to the nitrogen source is (1.10~2.50):1; the calcination temperature is 500~1500℃, and the time is 3~10h; the calcination is carried out under a protective atmosphere, and the protective atmosphere includes one of nitrogen and argon.

[0014] Preferably, the crown ether includes one or more of 18-crown-6, dibenzo-18-crown-6, dibenzo-30-crown-10, 15-crown-5 and cyclohexane-18-crown-6, and the mass ratio of the porous boron nitride powder to the crown ether is 10:(3~8).

[0015] Preferably, in step S1), the masses of the grinding beads during the ball milling process are 2.5 g, 10 g, 14 g, 15 g, and 55 g, respectively, and the quantity ratio is (14-16): (9-11): (4-6): (4-6): (2-4); the rotation speed of the ball mill is 300-500 r / min, and the time is 10-30 h.

[0016] Preferably, in step S2), the waste polyester includes one or more of waste polyester fibers, waste polyester plastics and waste polyester films.

[0017] Preferably, the mass ratio of the waste polyester, the ethylene glycol and the potassium carbonate is 1:(1.5-4.0):(0.015-0.05), the temperature of the alcoholysis reaction is 150-250° C., and the time is 1.5-5 h.

[0018] Preferably, the process further comprises stirring and secondary filtration after the hybrid material is added, and the stirring rate is 50-200 r / min.

[0019] The present application also provides a method for preparing a porous boron nitride@crown ether hybrid material, comprising the following steps:

[0020] The porous boron nitride micropowder, crown ether and water are mixed and freeze-dried to obtain a solid powder material;

[0021] The solid powder material is ball-milled to obtain a porous boron nitride@crown ether hybrid material.

[0022] Preferably, the mass ratio of the porous boron nitride powder to the crown ether is 10:(3-8).

[0023] The present application provides a method for recycling waste polyester alcoholysis by-products, which comprises the following steps: firstly, porous boron nitride micropowder, crown ether and water are mixed, and after hydrothermal deposition, the crown ether is uniformly adsorbed and deposited on the surface of the porous boron nitride, and then freeze-dried to stabilize the structure to obtain a solid powder material, and then the solid powder material is ball-milled to refine the material particles and enhance the interface bonding force between the porous boron nitride and the crown ether, thereby obtaining a porous boron nitride@crown ether hybrid material, and then, the unique powdery porous structure of the porous boron nitride@crown ether hybrid material is utilized to efficiently adsorb and chelate metal potassium ions after the waste polyester alcoholysis, so that the potassium ions are effectively shielded and removed, thereby realizing efficient and selective removal of potassium ions in the process of chemically recovering waste polyester. DETAILED DESCRIPTION

[0024] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0025] In view of the problem in the prior art that residual potassium ions in waste polyester alcoholysis byproducts affect the regeneration of alcoholysis byproducts, the present application provides a method for recycling waste polyester alcoholysis byproducts, which introduces a porous boron nitride@crown ether hybrid material with a unique powdery porous structure, and exhibits efficient adsorption and chelation capabilities for metal potassium ions during the chemical recovery of waste polyester, thereby achieving efficient removal of potassium ions during the alcoholysis recovery of waste polyester. Specifically, an embodiment of the present invention discloses a method for recycling waste polyester alcoholysis byproducts, comprising the following steps:

[0026] S1) mixing porous boron nitride micropowder, crown ether and water, performing hydrothermal deposition treatment and freeze drying to obtain a solid powder material;

[0027] Ball milling the solid powder material to obtain a porous boron nitride@crown ether hybrid material;

[0028] S2) performing alcoholysis reaction on waste polyester, ethylene glycol and catalyst potassium carbonate, and adding the hybrid material to the obtained reaction solution to remove potassium ions in the reaction solution.

[0029] The present application first mixes porous boron nitride micropowder, crown ether and water, and freeze-dries after hydrothermal deposition to obtain a solid powder material; in this process, porous boron nitride micropowder is first preferably prepared, which includes the following steps:

[0030] The boron source, the nitrogen source, the pore-forming agent and water are mixed, and then heated and dried to obtain a boron nitride precursor;

[0031] The boron nitride precursor is ground and then calcined to obtain porous boron nitride powder.

[0032] In the above preparation process, the boron source includes one or more of boric acid, ammonia borane, metaboric acid, boron chloride, boron oxide, boron sulfide and sodium borohydride, specifically, the boron source is selected from one of boric acid, ammonia borane, metaboric acid, boron chloride, boron oxide, boron sulfide and sodium borohydride, more specifically, the boron source is selected from boric acid, metaboric acid, boron chloride, boron sulfide, sodium borohydride or ammonia borane. The nitrogen source includes one or more of urea, melamine, sodium azide, dicyandiamide and sodium amide, specifically, the nitrogen source is selected from one of urea, melamine, sodium azide, dicyandiamide and sodium amide, more specifically, the nitrogen source is selected from urea, melamine, dicyandiamide or sodium azide. The pore-forming agent includes one or more of zinc acetate, nickel sulfate, cobalt sulfate, iron sulfate, copper sulfate and zinc sulfate. Specifically, the pore-forming agent is selected from one of zinc acetate, nickel sulfate, cobalt sulfate, iron sulfate, copper sulfate and zinc sulfate. More specifically, the pore-forming agent is selected from zinc acetate, copper sulfate, iron sulfate or zinc sulfate. The mass ratio of the boron source to the nitrogen source is (1.10-2.50):1. Specifically, the mass ratio of the boron source to the nitrogen source is (1.125-2.00):1. More specifically, the mass ratio of the boron source to the nitrogen source is (1.20-1.60):1. More specifically, the mass ratio of the boron source to the nitrogen source is (1.24-1.36):1. More specifically, the mass ratio of the boron source to the nitrogen source is (1.25-1.31):1. The mass ratio of the nitrogen source to the pore-forming agent is (15-21):1. Specifically, the mass ratio of the nitrogen source to the pore-forming agent is (18-20):1. The heating temperature is 80-120° C., specifically, the heating temperature is 95-110° C. The heating is performed to evaporate water to obtain a white boron nitride (BN) precursor.

[0033] The BN precursor is then ground and calcined to obtain porous BN powder. In this process, the grinding is a grinding method well known to those skilled in the art and is not particularly limited here; the calcination temperature is 500-1500°C and the time is 3-10 hours; the calcination is carried out under a protective atmosphere, and the protective atmosphere includes one of nitrogen and argon; specifically, the calcination temperature is 700-900°C and the time is 3.5-6 hours, and more specifically, the calcination temperature is 750-850°C and the time is 4-5 hours.

[0034] Boron nitride (BN), a two-dimensional material, is composed of hexagonal mesh crystals composed of nitrogen atoms and boron atoms. It has rich functional groups and a high specific surface area, and can effectively adsorb positively charged metal potassium ions. Further mixing and modifying it with crown ethers can enhance the reactive sites and greatly improve the adsorption capacity and stability of metal potassium ions. In addition, BN has good chemical inertness and thermal stability, and can withstand high temperature environments without decomposition or chemical changes. At the same time, BN also has high electrical insulation and thermal conductivity. By filling BN composites in the recycled resin matrix, the thermal conductivity and mechanical properties of the resin can be significantly improved.

[0035] After the porous boron nitride powder is prepared, it is mixed with a crown ether and water, and subjected to hydrothermal deposition treatment and freeze-dried to obtain a solid powder material; in this process, the crown ether includes one or more of 18-crown-6, dibenzo-18-crown-6, dibenzo-30-crown-10, 15-crown-5 and cyclohexane-18-crown-6, and specifically, the crown ether is selected from one of 18-crown-6, dibenzo-18-crown-6, dibenzo-30-crown-10, 15-crown-5 and cyclohexane-18-crown-6. The mass ratio of the porous boron nitride powder to the crown ether is 10: (3-8), specifically, the mass ratio of the porous boron nitride powder to the crown ether is 10: (5-7); more specifically, the mass ratio of the porous boron nitride powder to the crown ether is 10: 6. The hydrothermal deposition treatment is to uniformly adsorb and deposit the crown ether on the porous BN surface layer. After the hydrothermal deposition treatment, ultrasonic dispersion is preferably performed to ensure that the initial precipitation of the crown ether is fully mixed with each component; the temperature of the hydrothermal deposition treatment is 30-40°C, the time is 4-12h, and more specifically, the time of the hydrothermal deposition treatment is 8-10h. The time of the ultrasonic dispersion is 30-60min, and specifically, the time of the ultrasonic dispersion is 35-50min. The time of the freeze-drying is 25-30h.

[0036] According to the present invention, the solid powder material is then ball-milled to refine the material particles while enhancing the interfacial bonding force between the porous BN and the crown ether, thereby successfully preparing a porous BN@crown ether hybrid material. During the ball milling process, the masses of the grinding beads are 2.5g, 10g, 14g, 15g, and 55g, respectively, and the number ratio is (14-16): (9-11): (4-6): (4-6): (2-4). Specifically, the number ratio of the grinding beads in the ball mill is 15:10:5:5:3 to make the ball milling more complete. The rotation speed of the ball mill is 300-500r / min, and the time is 10-30h. Specifically, the rotation speed of the ball mill is 400-450r / min, and the time is 15-20h.

[0037] The present application then carries out alcoholysis reaction on waste polyester, ethylene glycol and catalyst potassium carbonate, and then adds the above hybrid material to the obtained reaction solution to remove potassium ions in the reaction solution; in this process, the waste polyester is a waste polyester material well known to those skilled in the art, and the present application has no special restrictions on its source and composition. For example, the waste polyester includes one or more of waste polyester fiber, waste polyester plastic and waste polyester film, and specifically, the waste polyester is selected from one of waste polyester fiber, waste polyester plastic and waste polyester film. The mass ratio of the waste polyester, the ethylene glycol and the potassium carbonate is 1: (1.5~4.0): (0.015~0.05), specifically, the mass ratio of the waste polyester, the ethylene glycol and the potassium carbonate is 1: (2~3): (0.025~0.03), and more specifically, the mass ratio of the waste polyester, the ethylene glycol and the potassium carbonate is 1: (2.3~2.5): (0.025~0.03). The alcoholysis reaction temperature is 150-250°C, and the time is 1.5-5h. Specifically, the alcoholysis reaction temperature is 175-215°C, and the time is 2-3.5h. More specifically, the alcoholysis reaction temperature is 197-205°C, and the time is 2.5-3h. Then, the hybrid material is added to the obtained reaction solution. The self-assembled porous BN@crown ether hybrid material has a unique powdery porous structure, and exhibits efficient adsorption and chelation ability for metal potassium ions in the chemical recycling process of waste polyester, and exhibits excellent shielding and removal performance; in the above process, it is preferred to remove potassium ions in the alcoholysis reaction solution by stirring and secondary filtration; the stirring rate is 50-200r / min, and specifically, the stirring rate is 80-150r / min.

[0038] Furthermore, the present application also provides a method for preparing a porous boron nitride@crown ether hybrid material, comprising the following steps:

[0039] The porous boron nitride micropowder, crown ether and water are mixed and freeze-dried to obtain a solid powder material;

[0040] The solid powder material is ball-milled to obtain a porous boron nitride@crown ether hybrid material.

[0041] The preparation of the porous boron nitride@crown ether hybrid material has been described in detail in the above content and will not be repeated here.

[0042] The porous boron nitride in the porous boron nitride@crown ether hybrid material prepared in the present application has a large pore size, which is more conducive to the efficient adsorption of metal potassium ions.

[0043] The present invention provides a method for recycling waste polyester alcoholysis byproducts, which successfully combines the strong metal ion adsorption of porous BN with the selective ion complexation of crown ether through the composite structure design of porous boron nitride@crown ether hybrid material, forming a highly efficient adsorption and shielding system for potassium ions; the prepared self-assembled porous BN@crown ether hybrid material has a good shielding effect on potassium ions during the chemical recovery of waste polyester. This technology can effectively eliminate the molecular chain capping effect that potassium carbonate may cause in the polymerization process of the late depolymerization product, and avoid the occurrence of nucleophilic-electrophilic and other side reactions in the subsequent polycondensation stage, thereby effectively improving the overall polymerization reaction efficiency and product quality.

[0044] In order to further understand the present invention, the method for recycling waste polyester alcoholysis by-products provided by the present invention is described in detail below in conjunction with embodiments, and the protection scope of the present invention is not limited by the following embodiments.

[0045] Example 1

[0046] (1) 2.43 g of boric acid, 1.85 g of urea and 0.10 g of zinc acetate were mixed and dissolved in ultrapure water, and the water was evaporated by stirring at 95 °C to obtain a white solid BN precursor; after grinding the precursor, it was heated to 800 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and calcined for 4 h to obtain porous BN powder;

[0047] (2) The porous BN powder and 18-crown-6 were uniformly dispersed in ultrapure water at a mass ratio of 10:6, and the mixed solution was placed in a shaker at 30°C for oscillation deposition for 4 h. After the oscillation deposition was completed, the mixed dispersion was ultrasonically dispersed for 40 min and then freeze-dried for 30 h. The obtained solid product was placed in a ball mill and ball-milled at 400 r / min for 15 h to obtain a porous BN@18-crown-6 hybrid material.

[0048] The powdered porous BN@18-crown-6 hybrid material prepared by the above method is directly used for potassium ion shielding in the depolymerization liquid of waste polyester fibers, and the process is as follows:

[0049] Waste polyester, ethylene glycol and catalyst potassium carbonate were put into the depolymerization reactor in a mass ratio of 1:2.5:0.025, and the alcoholysis reaction was carried out at 197°C for 2.5 hours. After the reaction was completed, the heating was stopped, and the depolymerization liquid was filtered with an industrial filter to remove the filter residue to obtain the final reaction liquid. Subsequently, the porous BN@18-crown-6 hybrid material was added to the reaction liquid, and the residual potassium ion content in the reaction liquid was measured after stirring and secondary filtration.

[0050] Example 2

[0051] (1) 2.52 g of boric acid, 1.85 g of melamine and 0.10 g of zinc acetate were mixed and dissolved in ultrapure water, and the water was evaporated by stirring at 85 °C to obtain a white solid BN precursor; the precursor was ground and heated to 750 °C at a heating rate of 5 °C / min in a nitrogen atmosphere, and calcined for 3 h to obtain porous BN powder;

[0052] (2) The porous BN powder and dibenzo-18-crown-6 were uniformly dispersed in ultrapure water at a mass ratio of 10:5, and the mixed solution was placed in a shaker at 30°C for oscillation deposition for 4 h. After the oscillation deposition was completed, the mixed dispersion was ultrasonically dispersed for 35 min and then freeze-dried for 25 h. The obtained solid product was placed in a ball mill and ball-milled at 450 r / min for 20 h to obtain a porous BN@dibenzo-18-crown-6 hybrid material.

[0053] The powdered porous BN@dibenzo-18-crown-6 hybrid material prepared by the above method is directly used for potassium ion shielding in the depolymerization liquid of waste polyester fibers, and the process is as follows:

[0054] Waste polyester, ethylene glycol and catalyst potassium carbonate were put into the depolymerization reactor in a mass ratio of 1:2:0.025, and the alcoholysis reaction was carried out at 200°C for 2 hours. After the reaction was completed, the heating was stopped, and the depolymerization liquid was filtered with an industrial filter to remove the filter residue to obtain the final reaction liquid. Subsequently, the porous BN@dibenzo-18-crown-6 hybrid material was added to the reaction liquid, and the residual potassium ion content in the reaction liquid was measured after stirring and secondary filtration.

[0055] Example 3

[0056] (1) 2.48 g of boric acid, 2.0 g of urea and 0.10 g of zinc acetate were mixed and dissolved in ultrapure water, and the water was evaporated by stirring at 90 °C to obtain a white solid BN precursor; after grinding, the precursor was heated to 850 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and calcined for 3.5 h to obtain porous BN powder;

[0057] (2) The porous BN powder and 18-crown-6 were uniformly dispersed in ultrapure water at a mass ratio of 10:5, and the mixed solution was placed in a shaker at 30°C for oscillation deposition treatment for 8 h. After the oscillation deposition was completed, the mixed dispersion was ultrasonically dispersed for 45 min, and then freeze-dried for 25 h. The obtained solid product was placed in a ball mill and ball-milled at a speed of 450 r / min for 20 h to obtain a porous BN / 18-crown-6 hybrid material.

[0058] The powdered porous BN / 18-crown-6 hybrid material prepared by the above method is directly used for potassium ion shielding in the depolymerization liquid of waste polyester fibers, and the process is as follows:

[0059] Waste polyester, ethylene glycol and catalyst potassium carbonate were put into a depolymerization reactor in a mass ratio of 1:2:0.03, and the alcoholysis reaction was carried out at 205°C for 2 hours. After the reaction was completed, the heating was stopped, and the depolymerization liquid was filtered using an industrial filter to remove the filter residue to obtain the final reaction liquid. Subsequently, the porous BN / 18-crown-6 hybrid material was added to the reaction liquid, and the residual potassium ion content in the reaction liquid was measured after stirring and secondary filtration.

[0060] Example 4

[0061] (1) 2.50 g of metaboric acid, 2.0 g of urea and 0.10 g of zinc acetate were mixed and dissolved in ultrapure water, and the water was evaporated by stirring at 95 °C to obtain a white solid BN precursor; after grinding the precursor, it was heated to 900 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and calcined for 3.5 h to obtain porous BN powder;

[0062] (2) The porous BN powder and 18-crown-6 were uniformly dispersed in ultrapure water at a mass ratio of 10:7, and the mixed solution was placed in a shaker at 30°C for oscillation deposition for 10 h. After the oscillation deposition was completed, the mixed dispersion was ultrasonically dispersed for 50 min, and then freeze-dried for 25 h. The obtained solid product was placed in a ball mill and ball-milled at a speed of 500 r / min for 20 h to obtain a porous BN@18-crown-6 hybrid material.

[0063] The powdered porous BN@18-crown-6 hybrid material prepared by the above method is directly used for potassium ion shielding in the depolymerization liquid of waste polyester fibers, and the process is as follows:

[0064] Waste polyester, ethylene glycol and catalyst potassium carbonate were put into the depolymerization reactor in a mass ratio of 1:2.3:0.03, and the alcoholysis reaction was carried out at 198°C for 2.5 hours. After the reaction was completed, the heating was stopped, and the depolymerization liquid was filtered with an industrial filter to remove the filter residue to obtain the final reaction liquid. Subsequently, the porous BN@18-crown-6 hybrid material was added to the reaction liquid, and the residual potassium ion content in the reaction liquid was measured after stirring and secondary filtration.

[0065] Example 5

[0066] (1) 2.50 g of boron chloride, 2.0 g of dicyandiamide and 0.10 g of copper sulfate were mixed and dissolved in ultrapure water, and the water was evaporated by stirring at 95 °C to obtain a white solid BN precursor; after grinding the precursor, it was heated to 800 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and calcined for 5 h to obtain porous BN powder;

[0067] (2) The porous BN powder and dibenzo-30-crown-10 were uniformly dispersed in ultrapure water at a mass ratio of 10:6, and the mixed solution was placed in a shaker at 30°C for oscillation deposition for 10 h. After the oscillation deposition was completed, the mixed dispersion was ultrasonically dispersed for 50 min and then freeze-dried for 30 h. The obtained solid product was placed in a ball mill and ball-milled at 450 r / min for 25 h to obtain a porous BN@dibenzo-30-crown-10 hybrid material.

[0068] The powdered porous BN@dibenzo-30-crown-10 hybrid material prepared by the above method is directly used for potassium ion shielding in the depolymerization liquid of waste polyester fibers, and the process is as follows:

[0069] Waste polyester, ethylene glycol and catalyst potassium carbonate were put into the depolymerization reactor in a mass ratio of 1:2:0.025, and the alcoholysis reaction was carried out at 198°C for 3 hours. After the reaction was completed, the heating was stopped, and the depolymerization liquid was filtered using an industrial filter to remove the filter residue to obtain the final reaction liquid. Subsequently, the porous BN@dibenzo-30-crown-10 hybrid material was added to the reaction liquid, and the residual potassium ion content in the reaction liquid was measured after stirring and secondary filtration.

[0070] Example 6

[0071] (1) 2.50 g of boron sulfide, 2.1 g of urea and 0.10 g of copper sulfate were mixed and dissolved in ultrapure water, and the water was evaporated by stirring at 95 °C to obtain a white solid BN precursor; after grinding, the precursor was heated to 850 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and calcined for 5 h to obtain porous BN powder;

[0072] (2) The porous BN powder and 15-crown-5 were uniformly dispersed in ultrapure water at a mass ratio of 10:5, and the mixed solution was placed in a shaker at 30°C for oscillation deposition for 12 h. After the oscillation deposition was completed, the mixed dispersion was ultrasonically dispersed for 60 min and then freeze-dried for 30 h. The obtained solid product was placed in a ball mill and ball-milled at 450 r / min for 25 h to obtain a porous BN@15-crown-5 hybrid material.

[0073] The powdered porous BN@15-crown-5 hybrid material prepared by the above method is directly used for potassium ion shielding in the depolymerization liquid of waste polyester fibers, and the process is as follows:

[0074] Waste polyester, ethylene glycol and catalyst potassium carbonate were put into the depolymerization reactor in a mass ratio of 1:2:0.025, and the alcoholysis reaction was carried out at 198°C for 3 hours. After the reaction was completed, the heating was stopped, and the depolymerization liquid was filtered with an industrial filter to remove the filter residue to obtain the final reaction liquid. Subsequently, the porous BN@15-crown-5 hybrid material was added to the reaction liquid, and the residual potassium ion content in the reaction liquid was measured after stirring and secondary filtration.

[0075] Example 7

[0076] (1) 2.50 g of sodium borohydride, 1.5 g of sodium azide and 0.10 g of ferric sulfate were mixed and dissolved in ultrapure water, and the water was evaporated by stirring at 90 °C to obtain a white solid BN precursor; after grinding the precursor, it was heated to 700 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and calcined for 5 h to obtain porous BN powder;

[0077] (2) The porous BN powder and cyclohexane-18-crown-6 were uniformly dispersed in ultrapure water at a mass ratio of 10:8, and the mixed solution was placed in a shaker at 30°C for oscillation deposition for 10 h. After the oscillation deposition was completed, the mixed dispersion was ultrasonically dispersed for 60 min and then freeze-dried for 25 h. The obtained solid product was placed in a ball mill and ball-milled at 420 r / min for 20 h to obtain a porous BN@cyclohexane-18-crown-6 hybrid material.

[0078] The powdered porous BN@cyclohexane-18-crown-6 hybrid material prepared by the above method is directly used for potassium ion shielding in the depolymerization liquid of waste polyester fibers, and the process is as follows:

[0079] Waste polyester, ethylene glycol and catalyst potassium carbonate were put into the depolymerization reactor in a mass ratio of 1:2:0.03, and the alcoholysis reaction was carried out at 197°C for 2.5 hours. After the reaction was completed, the heating was stopped, and the depolymerization liquid was filtered with an industrial filter to remove the filter residue to obtain the final reaction liquid. Subsequently, the porous BN@cyclohexane-18-crown-6 hybrid material was added to the reaction liquid, and the residual potassium ion content in the reaction liquid was measured after stirring and secondary filtration.

[0080] Example 8

[0081] (1) 2.25 g of ammonia borane, 2.0 g of urea and 0.10 g of zinc sulfate were mixed and dissolved in ultrapure water, and the water was evaporated by stirring at 90 °C to obtain a white solid BN precursor. After grinding, the precursor was heated to 800 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and calcined for 5 h to obtain porous BN powder;

[0082] (2) The porous BN powder and 18-crown-6 were uniformly dispersed in ultrapure water at a mass ratio of 10:8, and the mixed solution was placed in a shaker at 30°C for oscillation deposition for 10 h. After the oscillation deposition was completed, the mixed dispersion was ultrasonically dispersed for 60 min, and then freeze-dried for 25 h. The obtained solid product was placed in a ball mill and ball-milled at 420 r / min for 20 h to obtain a porous BN@18-crown-6 hybrid material.

[0083] The powdered porous BN@18-crown-6 hybrid material prepared by the above method is directly used for potassium ion shielding in the depolymerization liquid of waste polyester fibers, and the process is as follows:

[0084] Waste polyester, ethylene glycol and catalyst potassium carbonate were put into the depolymerization reactor in a mass ratio of 1:3:0.03, and the alcoholysis reaction was carried out at 197°C for 3.5 hours. After the reaction was completed, the heating was stopped, and the depolymerization liquid was filtered with an industrial filter to remove the filter residue to obtain the final reaction liquid. Subsequently, the porous BN@18-crown-6 hybrid material was added to the reaction liquid, and the residual potassium ion content in the reaction liquid was measured after stirring and secondary filtration.

[0085] Comparative Example 1

[0086] 2.43g boric acid, 1.85g urea and 0.10g zinc acetate were mixed and dissolved in ultrapure water, and the water was evaporated by stirring at 95°C to obtain a white solid BN precursor. After grinding, the precursor was heated to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere and calcined for 4h to obtain porous BN powder;

[0087] The porous BN powder prepared by the above method is directly used for potassium ion shielding in the alcoholysis and depolymerization liquid of waste polyester fiber, and the process is as follows:

[0088] Waste polyester, ethylene glycol and catalyst potassium carbonate were put into the depolymerization reactor in a mass ratio of 1:2.5:0.025, and the alcoholysis reaction was carried out at 197°C for 2.5 hours. After the reaction was completed, the heating was stopped, and the depolymerization liquid was filtered with an industrial filter to remove the filter residue to obtain the final reaction liquid. Subsequently, porous BN micropowder was added to the reaction liquid, and the residual potassium ion content in the reaction liquid was measured after stirring and secondary filtration.

[0089] Comparative Example 2

[0090] Waste polyester, ethylene glycol and catalyst potassium carbonate were put into the depolymerization reactor in a mass ratio of 1:2.5:0.025, and the alcoholysis reaction was carried out at 197°C for 2.5 hours. After the reaction was completed, the heating was stopped, and the depolymerization liquid was filtered with an industrial filter to remove the filter residue to obtain the final reaction liquid. Subsequently, 18-crown-6 was added to the reaction liquid, and the residual potassium ion content in the reaction liquid was measured after stirring and secondary filtration.

[0091] The potassium ion removal rates in the above-mentioned embodiments and comparative examples are shown in Table 1:

[0092] Table 1 Data table of potassium ion removal rate in depolymerization solution

[0093]

[0094] As can be seen from Table 1, by analyzing the results of Examples 1 to 8, by adjusting the boron source, nitrogen source and pore-forming agent in the preparation process of porous BN and self-assembling with the crown ether, the prepared hybrid material has achieved good effect in shielding potassium ions during the alcoholysis of waste polyester.

[0095] The results of Comparative Examples 1 and 2 show that under the same depolymerization conditions of waste polyester, the addition of porous BN micropowder or 18-crown-6 alone has a poor shielding effect on potassium ions in the reaction solution. It can be seen that there is an obvious synergistic effect between the porous BN and the crown ether in the present invention in shielding potassium ion pairs.

[0096] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0097] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for recycling waste polyester alcoholysis byproducts, comprising the following steps: S1) mixing porous boron nitride micropowder, crown ether and water, performing hydrothermal deposition treatment and freeze drying to obtain a solid powder material; Ball milling the solid powder material to obtain a porous boron nitride@crown ether hybrid material; S2) performing alcoholysis reaction on waste polyester, ethylene glycol and catalyst potassium carbonate, and adding the hybrid material to the obtained reaction solution to remove potassium ions in the reaction solution.

2. The recycling method according to claim 1, characterized in that: The preparation method of the porous boron nitride powder is specifically as follows: The boron source, the nitrogen source, the pore-forming agent and water are mixed, and then heated and dried to obtain a boron nitride precursor; The boron nitride precursor is ground and then calcined to obtain porous boron nitride powder.

3. The recycling method according to claim 2, characterized in that: The boron source includes one or more of boric acid, ammonia borane, metaboric acid, boron chloride, boron oxide, boron sulfide and sodium borohydride; the nitrogen source includes one or more of urea, melamine, sodium azide, dicyandiamide and sodium amide; the pore-forming agent includes one or more of zinc acetate, nickel sulfate, cobalt sulfate, iron sulfate, copper sulfate and zinc sulfate; the mass ratio of the boron source to the nitrogen source is (1.10-2.50):1; the calcination temperature is 500-1500°C, and the time is 3-10h; the calcination is carried out under a protective atmosphere, and the protective atmosphere includes one of nitrogen and argon.

4. The recycling method according to claim 1, characterized in that: The crown ether includes one or more of 18-crown-6, dibenzo-18-crown-6, dibenzo-30-crown-10, 15-crown-5 and cyclohexaned-18-crown-6, and the mass ratio of the porous boron nitride powder to the crown ether is 10:(3~8).

5. The recycling method according to claim 1, characterized in that: In step S1), the masses of the grinding beads during the ball milling process are 2.5 g, 10 g, 14 g, 15 g, and 55 g, respectively, and the quantity ratio is (14-16): (9-11): (4-6): (4-6): (2-4); the rotation speed of the ball mill is 300-500 r / min, and the time is 10-30 h.

6. The recycling method according to claim 1, characterized in that: In step S2), the waste polyester includes one or more of waste polyester fibers, waste polyester plastics and waste polyester films.

7. The recycling method according to claim 1, characterized in that: The mass ratio of the waste polyester, the ethylene glycol and the potassium carbonate is 1: (1.5-4.0): (0.015-0.05), the temperature of the alcoholysis reaction is 150-250° C., and the time is 1.5-5 hours.

8. The recycling method according to claim 1, characterized in that: After adding the hybrid material, stirring and secondary filtration are also performed, and the stirring rate is 50-200 r / min.

9. A method for preparing a porous boron nitride@crown ether hybrid material, comprising the following steps: The porous boron nitride micropowder, crown ether and water are mixed and freeze-dried to obtain a solid powder material; The solid powder material is ball-milled to obtain a porous boron nitride@crown ether hybrid material.

10. The preparation method according to claim 9, characterized in that: The mass ratio of the porous boron nitride powder to the crown ether is 10:(3-8).

Citation Information

Patent Citations

  • Method for preparing regenerated polyester through efficient alcoholysis of waste polyester

    CN113214458A

  • Small-particle-size spherical hexagonal boron nitride nano-powder and preparation method thereof

    CN119079938A

  • Highly filling boron nitride powder

    JP2000007310A

  • Precision processing equipment for cutting materials

    KR102759848B1

  • Polyester composition and method for producing the same

    US6020421A

Cited By

  • Carbon fiber reinforced resin-based composite material and preparation method thereof

    CN121064504A